INFLUENCE OF PHOSPHATE SOLUBILIZING BACTERIA ON THE METABOLIC PARAMETERS AND GROWTH OF CARROT PLANTS (DAUCUS CAROTA L.) IN KODAI HILLS OF TAMILNADU, INDIA - U., Muthuvel; B., Harinathan; K. , Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Daucus carota is an important vegetable which is ranked third among the succulent vegetables in world production. Excessive amount of inorganic fertilizer results in soil acidification, increased greenhouse gas (GHG) emissions, and increased eutrophication of water bodies, can be mitigated by soil amendment using PSB bio-fertilizers, which resulted in improved plant growth and productivity. In this present study, the chosen potential PSB strains Micrococcus luteus, Paenibacillus polymyxa after characterization were selected for inoculation, and the field experiment was conducted using randomized complete block design with three replications, and the influence of these phosphate solubilizers on the growth, yield and metabolism parameters were evaluated after growth of carrot plants. Both PSB strains showed higher than 180 (phosphate solubilisation efficiency), and reduced pH from 8.0 to below 6.0 indicates high phosphate solubilising efficiency, increased organic acid production, when treated with plants Carrot Test (CT) - (11-15), they tend to enhance the vegetative growth, yield and qualitative parameters of carrot plants when compared to other treatments Carrot Test (CT) - (1-5), Carrot Test (CT) - (6-10). The application of Phosphate-Solubilizing Bacteria (PSB) bio-fertilizers Carrot Test (CT) - (11-15) in combination with calcium phosphate would aid uptake of phosphorus for better crop growth and yield and under a long run would aid to substantially sustainable soil fertility.